2022
DOI: 10.1002/aenm.202202913
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Interfacial Charge Transfer of Epitaxially Grown Ir Clusters for Boosting Hydrogen Oxidation Reaction

Abstract: The sluggish kinetics of hydrogen oxidation reaction (HOR) is one of the critical challenges for anion exchange membrane fuel cells. Here, we report epitaxial growth of Ir nanoclusters (<2 nm) on a MoS2 surface (Ir/MoS2) and optimize the alkaline HOR activity via tailoring interfacial charge transfer between Ir clusters and MoS2. The electron transfer from MoS2 to Ir clusters can effectively prevent the oxidation of Ir clusters, which is not the case for carbon‐supported Ir nanoclusters (Ir/C) synthesized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Yan and colleagues recently have shown that the hydrogen binding energies (HBEs), as indicated by the voltammetric peaks associated with the underpotential deposition hydrogen (H upd ), reasonably account for the nearly linear decrease in specific activities for HOR/HER on a variety of polycrystal noble metal catalysts with the increasing electrolyte pH. These facts seem to strengthen the general idea that the HBEs can serve as the sole activity descriptor of catalysts for HOR/HER, while hydroxide binding energies (OHBEs) have trivial impact. On the other hand, results from experiments and simulations challenging this idea are as common as those that support it. Numerous studies have shown that the activity for HOR/HER in alkaline media can be promoted by increasing the OHBE/oxophilicity of the catalyst surface, for example, modification of Pt with oxophilic Ni­(OH) 2 islands or Ru atoms. , On this basis, Markovic et al have proposed the bifunctional mechanism for hydrogen electrode reactions that highlights the crucial role of OHBE toward the dissociation and/or formation of interfacial H 2 O molecules. , In addition, McCrum and Koper have shown, through both experimental observation and theoretical model, that the kinetics of HER should also have volcano dependences on OHBE owing to the switch of the rate-determining step from water dissociation to OH ad desorption with increasing OHBE . More importantly, they reckoned that the activation barrier of water dissociation is linearly related to the OHBE of catalysts, no matter whether the OH ad is involved or not.…”
Section: Introductionmentioning
confidence: 99%
“…Yan and colleagues recently have shown that the hydrogen binding energies (HBEs), as indicated by the voltammetric peaks associated with the underpotential deposition hydrogen (H upd ), reasonably account for the nearly linear decrease in specific activities for HOR/HER on a variety of polycrystal noble metal catalysts with the increasing electrolyte pH. These facts seem to strengthen the general idea that the HBEs can serve as the sole activity descriptor of catalysts for HOR/HER, while hydroxide binding energies (OHBEs) have trivial impact. On the other hand, results from experiments and simulations challenging this idea are as common as those that support it. Numerous studies have shown that the activity for HOR/HER in alkaline media can be promoted by increasing the OHBE/oxophilicity of the catalyst surface, for example, modification of Pt with oxophilic Ni­(OH) 2 islands or Ru atoms. , On this basis, Markovic et al have proposed the bifunctional mechanism for hydrogen electrode reactions that highlights the crucial role of OHBE toward the dissociation and/or formation of interfacial H 2 O molecules. , In addition, McCrum and Koper have shown, through both experimental observation and theoretical model, that the kinetics of HER should also have volcano dependences on OHBE owing to the switch of the rate-determining step from water dissociation to OH ad desorption with increasing OHBE . More importantly, they reckoned that the activation barrier of water dissociation is linearly related to the OHBE of catalysts, no matter whether the OH ad is involved or not.…”
Section: Introductionmentioning
confidence: 99%
“…2(d) and Table S2 (ESI†) summarize and compare the two mass-specific values of different precious metal based HOR electrocatalysts reported in the literature as well as the commercial benchmark catalysts. 12,14,23–36 Remarkably, the j k,m value of our Ni@IrNi is about four-fold greater than those of 20 wt% Ir/C and 20 wt% Pt/C, and significantly exceeds that of 20 wt% PtRu/C; its j 0,m value is about twice greater than those of 20 wt% Ir/C and 20 wt% Pt/C as well as 20 wt% PtRu/C (Fig. S13, ESI†).…”
Section: Resultsmentioning
confidence: 89%
“…the literature as well as the commercial benchmark catalysts. 12,14,[23][24][25][26][27][28][29][30][31][32][33][34][35][36] Remarkably, the j k,m value of our Ni@IrNi is about four-fold greater than those of 20 wt% Ir/C and 20 wt% Pt/C, and significantly exceeds that of 20 wt% PtRu/C; its j 0,m value is about twice greater than those of 20 wt% Ir/C and 20 wt% Pt/C as well as 20 wt% PtRu/C (Fig. S13, ESI †).…”
Section: Energy and Environmental Science Papermentioning
confidence: 99%
See 2 more Smart Citations